PENGARUH PERHATIAN ORANG TUA DISIPLIN BELAJAR DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI DI KOTA PADANG - Zamris Zamris; Sri Ulfa Sentosa (Program Magister Pendidikan Ekonomi (S2), 2016)
This study aims to determine the effect of parental supervision, discipline and creativity of students learning the learning outcomes of students of class X on economic subjects the second semester of academic year 2012/2013 Senior High School in the town of Padang. This type of research is descriptive and associative research is research that aims to determine how far the independent variables affect the dependent variable. Data is primary data obtained directly through the questionnaire. The population in this study were all students of class X SMA in the city of Padang, which amounted to 4,547 people. This study using proportional random sampling technique to obtain samples so that all the population of 369 people sampled. The data is processed by using multiple regression analysis. Based on the analysis of the study concluded that (1) Attention parents positive significant effect on learning outcomes, which thitung> ttable that is equal to 2.728> 1.984 so the first hypothesis is accepted. (2) Discipline learned significant effect on learning outcomes, where t count> t table that is equal to 2.823> 1.984 so that the second hypothesis is accepted (3) Creativity significant effect on students' learning outcomes, where t count> t table that is equal to 3.235> 1.984 to 3 accepted hypothesis (4 ) Discipline learning, family and school environment significantly influence student achievement, where Fhitung> Ftabel that is equal to 8.011> 2,60 so that hypothesis 4 is accepted. Results of this study that concern parents, discipline and creativity of students learning has a significant influence on the results of class X student of SMA in the city of Padang. Form variables influence of parental supervision, discipline and creativity of students learning to student learning outcomes are positive. This means that the higher the parents' attention, learning discipline and creativity of the students will be higher the learning outcomes of students of class X SMA in Padang. Keywords: Attention parents, Discipline student learning and Creativity, Learning Outcomes.